Variations of heart rate variability parameters prior to the onset of ventricular tachyarrhythmia and sinus tachycardia in ICD patients. Results from the heart rate variability analysis with automated ICDs (HAWAI) registry. (22nd April 2015) - Wollmann, C G; Gradaus, R; Böcker, D; Fetsch, T; Hintringer, F; Hoh, G; Hatala, R; Podczeck-Schweighofer, A; Kreutzer, U; Kamaryt, P; Hauser, T; Kersten, J F; et al.
Abstract: The HAWAI registry evaluated the role of heart rate variability in predicting the occurrence of ventricular tachycardia and fibrillation (VT/VF) and sinus tachycardia in patients with an implantable cardioverter-defibrillator (45 patients with 155 RR recordings). A significant decrease of the mean value of all RR intervals (MeanNN) was observed in the period starting 20 and 40 min prior to VT/VF and sinus tachycardia, respectively. The standard deviation of RR intervals (SDNN) and the power at low frequency (LF) were the only parameters with significant changes prior to VT/VF. For sinus tachycardia, the root mean square of successive differences of all successive RR intervals (r-MSSD) and the power at low and high frequency (HF) decreased, whereas SDNN and the power at very low frequency increased. Comparison of RR recordings preceding VT/VF and sinus tachycardia revealed significant differences of the MeanNN, SDNN, r-MSSD, LF and HF. Based on a classification and regression tree analysis, MeanNN, SDNN and r-MSSD showed a sensitivity of 94.4% and a specificity of 50.6% as predictors of VT/VF. Our results suggest that the temporal changes in heart rate before an arrhythmic event can be used to predict the occurrence of VT/VF. These parameters may be used to optimize pacing therapies designed to prevent VT/VF recurrences as well as for improving device-based discriminators for VT/VF and sinus tachycardia.